Shifting From Warriors to Guardians: Officer Reflections on Law Enforcement Training in Washington State - Strah, Beck (Crime & delinquency, 2023)
Contemporary law enforcement methods are largely defined by crime control and militarization in the ?warrior? policing model. In 2013, the Washington State Criminal Justice Training Commission (WSCJTC) adopted an alternative ?guardian? training model for the Basic Law Enforcement Academy (BLEA) focused on procedural justice, community partnerships, de-escalation, and crisis intervention. The current study investigates BLEA graduates? perceptions of guardian policing and training elements. Researchers interviewed new officers who completed BLEA training with the guardian curriculum (n?=?17) and officers trained in a warrior-based curriculum (n?=?11). Themes are analyzed from interview data, including officer perceptions of BLEA guardian training and related programs. The paper concludes with discussion of limitations, themes, and policy implications of the research.